Bahasa Inggris - Anik Cahyaning Rahayu; Sudarwati Sudarwati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2023)
Family is one of the most important social institutions and primary groups in society. It is a social group consisting of members related to one another by blood and marital ties. There are several functions of family, such as economic, educational, religious, prestige, protecting, recreational, and affecting function. If the functions above fail to be fulfilled in the family, this condition is called a family dysfunction. Family dysfunction is any condition that interferes with healthy family functioning. This article is about family dysfunction in Rainbow Rowell's Fangirl as the data source. This research applies the qualitative research design meanwhile the approach used is sociological. Two problems that will be discussed in this research are the causes and the effects of family dysfunction experienced by the Avery family in the novel. The family is characterized by a range of dysfunctional dynamics that impact each member of the family. The family consists of the father, Athur, the mother, Laura, and the twin daughters, Cath and Wren. Athur suffers from mental illness and Laura leaves the family. Both facts are examples of the causes of family dysfunction, while the examples of its effects are that Cath and Wren suffer from anxiety and depression. Family dysfunction is a general problem that may happen to other families. Analyzing literary depictions of family dysfunction also highlights the need for social support systems and policy interventions to address common sources of family problems. The complex character portrayals in Fangirl provide a vivid and nuanced representation of dysfunctional family dynamics, underscoring the importance of functional families for individual and societal well-being.